Analisis Metode Bernyanyi pada Pengembangan Bahasa Anak Usia Dini di RA As-Syarif Sibanggor Jae - Trini Dama Yanti; Sartika Dewi Harahap; Syamsiah Depalina Siregar (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
Name: Trini Dama Yanti. Student ID: 20030041. This thesis discusses the analysis of singing methods in early childhood language development at RA As-Syarif, Sibanggor Jae village. The research aims to determine (1) the language development of early childhood at RA As-Syarif and (2) the effectiveness of the singing method in supporting language development. This qualitative study employs a descriptive approach, describing data processing results through observation, interviews, and documentation. Data were analyzed in three stages: data reduction, data presentation, and conclusion drawing. The results indicate significant progress in children's language development at RA As-Syarif, particularly in symbolic and complex language use. The singing method has proven effective in enhancing vocabulary, speaking skills, and children's confidence. This research concludes that the singing method creates a fun learning environment that supports early childhood language development.